Research on Modeling Intrahousehold Interactions from the Perspective of Space-Time Constraints. (9th February 2017) - Gao, Liangpeng; Ji, Yanjie; Liu, Yang; He, Baohong
Abstract : Interactions among family members can yield valuable information for interpreting individual travel decisions. Typically, each family member plays a set role and travel decisions are made by considering the combined needs of household members. This study investigates both multiactivity and multiperson interactions in urban nuclear families and proposes the novel concepts of "activity-restriction degree" and "activity-constraint niche" to quantify the degree of space-time constraints within time geography. A structural equation model is employed to analyze intrahousehold interactions based on individual activity-travel patterns during the workday. The results indicate that the links between family members reflect behavioral responses (with constraints) between individuals and other family members. Household interaction constraints not only influence individual travel decisions but also affect the realization of the household activity for everyone. These interactions lead to reasonable adjustments and mutual support and to the identification of efficient activity patterns that meet the demands of the entire household.